Periodic electron motion in the field of intensive plane light wave - Grigor’ev, Yu.N.; Zvonaryova, O.D. (Вопросы атомной науки и техники, 2001)
Results of integration of the Lorentz-Dirac equation for electron motion in the field of intensive light wave are given in this work. Diagrams and parameters, which characterize the periodic motion of a relativistic electron, are shown. Formulas of the spectral-angular distribution of the electromagnetic field irradiated by a relativistic electron, moving towards electromagnetic wave, were obtained.